Sosio-histories een sosiologie se interpretasie van die nuwe Testament* - Botha, Jan (Koers, 1989)
Contemporary social and political developments on a global scale prompted a renewed interest in the study of the social facets of the New Testament d u r in g the past decade or so. The purpose of this article is to give an overview of the progress made in this line of questioning . More specifically, the article has as its aim to propose a set of categories in terms of which the two main approaches within this branch of New Testament studies can be clearly and consistently distinguished - a matter on which there is currently much confusion. These two approaches are (i) a description of social aspects of the New Testament based on historical-critical methodology, and (ii) an interpretation of the social data thus collected, based on modern social-scientific methodology (specifically Sociology and Anthropology ) . It is argued that there is ample room as well as a need for the practice of both these approaches, despite the disagreements between the proponents of the two schools. An important aspect of my argumentation is to give relatively elaborate illustrations of each approach.